Knowledge, attitude and practice of mammography among women users of public health services Conhecimento, atitude e prática da mamografia entre usuárias do serviço público de saúde - Luiz Alberto Barcelos Marinho; José Guilherme Cecatti; Maria José Duarte Osis; Maria Salete Costa Gurgel (Universidade de São Paulo, 2008)
OBJECTIVE: To evaluate knowledge, attitude and practice related to mammography among women users of local health services, identifying barriers to its performance. METHODS: A total of 663 women were interviewed at 13 local health centers in a city of Southeastern Brazil, in 2001. Interviewees were randomly selected at each center and they were representative from different socioeconomic conditions. The number of interviewees at each center was proportional to monthly mean appointments. For data analysis, answers were described as knowledge, attitude, practice and their respective adequacies and then they were correlated with control variables through the chi-square test. RESULTS: Only 7.4% of the interviewees had adequate knowledge on mammography, while 97.1% of women had an adequate attitude. The same was seen for the practice of mammography that was adequate in 35.7% of the cases. The main barrier to mammography was lack of referral by physicians working at the health center (81.8%). There was an association between adequacy of attitude and five years or more of education and being married. There was also an association between adequacy of mammography practice and being employed and family income up to four minimum wages. CONCLUSIONS: Women users of local health services had no adequate knowledge and practice related to mammography despite having an adequate attitude about this exam. OBJETIVO: Avaliar o conhecimento, a atitude e a prática do exame de mamografia entre as mulheres usuárias do serviço médico municipal, identificando as barreiras para seu acesso à realização do procedimento. MÉTODOS: Foram entrevistadas 663 mulheres de 13 centros de saúde municipais de Campinas, SP, em 2001. As entrevistadas foram incluídas de forma aleatória, representando diferentes estratos sociais. O número de entrevistas em cada centro de saúde foi proporcional ao número médio mensal de mulheres atendidas. As respostas foram descritas quanto ao conhecimento, atitude e prática e suas respectivas adequações. A adequação foi correlacionada com variáveis de controle utilizando o teste qui-quadrado. RESULTADOS: Apenas 7,4% das entrevistadas tinham conhecimento adequado sobre o exame de mamografia, embora a atitude frente a este procedimento tenha sido adequada em 97,1% das mulheres e a prática adequada em 35,7% das entrevistadas. A principal barreira para a realização da mamografia foi a não solicitação por parte dos médicos dos centros de saúde (81,8%). A adequação da atitude esteve relacionada à escolaridade igual ou superior a cinco anos e ser casada. A prática adequada da mamografia associou-se com o trabalho fora de casa e renda familiar igual ou superior a cinco salários mínimos. CONCLUSÕES: O conhecimento e a prática da mamografia entre as usuárias do serviço médico municipal foi inadequada, apesar da atitude adequada em relação ao procedimento.